Drug Injection to Sites other than Arm: A Study of Iranian Heroin Injectors - Karimi, Mehrdad; Ghaheri, Hafez; Assari, Shervin; Moghani Lankarani, Reza; Moghani Lankarani, Maryam; Rafiey, Hassan; Narenjiha, Hooman; Ahmadi, Khodabakhsh; Tavakoli, Mahmood; Jafari, Firoozeh (Frontiers in Psychiatry, 2014)
For almost all injecting drug users (IDUs), the first site of injection is the arm. Years after injection, IDUs may shift to using other sites for intravenous (IV) access. Although injection to sites other than the arm is associated with higher risks, literature is limited regarding this behavior. We aimed to determine the prevalence and associated factors of using IV access points other than the arm among a national sample of IDUs in Iran. Data came from the National Drug Dependence Survey, 2007, which had enrolled 863 IDUs with at least one daily injection. Data on socio-demographics, pattern of drug use, and injection-related behaviors were entered into a logistic regression to determine predictors of injection to sites other than the arm. From all participants, 54.8% reported current injection sites in areas other than the arm. The other injection sites were the femoral venous sinus (17.0%), followed by the groin (14.5%) and neck (11.5%). Logistic regression revealed that living alone [odds ratio (OR) = 1.789, 95% confidence interval (CI) = 1.218–2.629], being Sunni (OR = 3.475, 95% CI = 1.775–6.801), having higher family income (OR = 1.002, 95% CI = 1.001–1.003), higher age at first drug use (OR = 1.039, 95% CI = 1.009–1.069), longer injection duration (OR = 1.071, 95% CI = 1.041–1.102), and more injection frequency (OR = 1.255, 95% CI = 1.072–1.471) were associated with higher likelihood of using injection sites other than the arm. Using sites other than the arm for IV injection is linked to socio-demographics, drug use data, and injection-related characteristics that can be used by policy makers. This information can be used for harm reduction planning.